Golden Gate Bridge Looking Toward Treasure Island on San Francisco Bay (H.S. Crocker Co., Inc.)
The Golden Gate Bridge, spanning the entrance to San Francisco Bay, overlooks Treasure Island, man-made site of the 1939 Golden Gate International Exposition. In the right background the 8 1/4 mile San Francisco-Oakland Bay Bridge. In the left background, Alcatraz Island.